Hand in hand into the unknown:the potential of experimental intercultural collaboration in Music in Africa - Ligeti, Lukas (My University, 2020)
Various forms of African music are of great significance to me as a composer and musician, and since 1994, I have worked consistently on projects with musician colleagues from West Africa. This led to several CDs and concert tours, but also to the emergence of an approach to crosscultural work that I have come to call experimental intercultural collaboration. In this thesis, I present the cultural and theoretical frameworks and positions that lie at the foundation of this approach and analyze some of its musical results. I recount the stories of two ensembles I cofounded, one based in Côte d’Ivoire and the other in Burkina Faso; reflect on the impact of African music on my works for Western ‘classical’ groups; and provide extensive analysis of music generated in all of these environments. This is framed by chapters reporting on the reception of this work by the press and my collaborators as well as broader historical and ethnomusicological considerations and personal aesthetic and humanistic viewpoints. I attempt to give a comprehensive overview of the concepts underlying my experimental intercultural work and of the research and creative processes involved in these collaborations.
A thesis submitted to the Faculty of Humanities University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Degree of Doctor of Philosophy in Music Composition,1 June 2020